Donor Utilization in the Recent Era: Effect of Sex, Drugs, and Increased Risk. (21st June 2022) - Baran, David A.; Long, Ashleigh; Lansinger, Justin; Copeland, Jack G.; Copeland, Hannah
Abstract : Background: Heart transplantation volumes have increased in recent years, yet less than a third of donors are typically accepted for transplantation. Whether donor sex, donor drug use, or perception of increased risk affects utilization for transplantation is unclear. Methods: The United Network for Organ Sharing database was queried for donors from January 1, 2007, to December 31, 2017. Donor toxicology was collected when available. Multivariate analysis was conducted to examine correlations with donor utilization. Results: Between January 1, 2007, and December 31, 2017, there were 87 816 heart donors aged ≥15 years. The mean age was 42.7±15.8 years, and 24 831 donors (28.3%) were utilized for heart transplantation. Subsequent analyses focused on donors between 15 and 39 years old. The strongest associations with donor acceptance were for male donor sex, blood type, hepatitis C antibody, donor age, left ventricular hypertrophy, and history of donor drug use. After removing hepatitis C, Public Health Service Increased Risk was identified as a strong negative predictor. Most positive drug toxicology results were associated with donor nonuse except for donors between 15 and 19 years of age. Exceptions included alcohol, marijuana, and cocaine. Opiates were associated with less utilization at all donor ages. The Public Health Service Increased Risk status was associated with significantly less utilization in all age groups except 15- to 19-year-old donors. Conclusions: While male donors were preferentially utilized, donors with drug use or those deemed Public Health Service Increased Risk were significantly less utilized for heart transplantation. Further consideration of such donors would be appropriate particularly as the demand for transplantation continues to increase.